Implicações éticas do transplante de órgãos entre animais não-humanos e humanos: uma avaliação crítica do xenotransplante - Coelho, Gustavo Henrique de Freitas (2023)
Among the alternatives investigated to address the deficit of organs available for transplant is the use of non-human animals as organ providers, a technique known as xenotransplantation. Although the first experiments of this kind date back more than a century, and research has progressed in recent decades driven by advances in genetic manipulation, the procedure remains unfamiliar to a large portion of the population, with scant discussion about its challenges and ethical implications. Thus, this study has a dual purpose: (a) to consolidate relevant data that highlights the complexity that goes beyond the clinical execution of the procedure, providing elements for an ethical analysis of xenotransplantation, and (b) to promote critical reflection and encourage others to engage in a rigorous and detailed discussion on the subject. Reflecting this concern, the work was structured into two sections. The first section, of a descriptive nature, compiles technical-scientific information. Chapter 1 delves into the complexities, challenges, and limitations of the traditional transplant system. In Chapter 2, a historical overview of xenotransplantation is outlined, prioritizing organ xenotransplantation. The second section presents the ethical dilemmas arising from xenotransplantation. In Chapter 3, we address the balance between the (possible) individual rights of patients to receive organs of animal origin and the collective risks associated with xenozoonoses; concerns related to the monitoring and potential invasion of privacy of xenotransplanted patients and their close relatives; challenges and limitations in the process of free and informed patient consent; the stance of the health system towards patients who decline organs of animal origin or choose xenotransplantation; recent cases of the use of brain-dead patients in organ xenotransplantation experiments and their possible repercussions; and finally, we dedicate ourselves to reflecting on the use of non-human animals, focusing on the justifications that seek to legitimize this use. The chapters have been structured in such a way that, together, they establish a continuous narrative, where the analysis of concepts, arguments, and concerns in one chapter leads to the subsequent theme. By the end, I hope they outline a comprehensive panorama of the issues involved and provide a well-founded and coherent argumentation that supports the conclusion that the practice of organ xenotransplantation should be abandoned and evaluated as morally wrong.